Bacterial Community Dynamics in an Oyster Hatchery in Response to Probiotic Treatment - Stevick, Rebecca J.; Sohn, Saebom; Modak, Tejashree H.; Nelson, David R.; Rowley, David C.; Tammi, Karin; Smolowitz, Roxanna; Markey Lundgren, Kathryn; Post, Anton F.; Gómez-Chiarri, Marta (Frontiers in Microbiology, 2019)
Larval oysters in hatcheries are susceptible to diseases caused by bacterial pathogens, including Vibrio spp. Previous studies have shown that daily addition of the probiotic Bacillus pumilus RI06-95 to water in rearing tanks increases larval survival when challenged with the pathogen Vibrio coralliilyticus. We propose that the presence of probiotics causes shifts in bacterial community structure in rearing tanks, leading to a net decrease in the relative abundance of potential pathogens. During three trials spanning the 2012-2015 hatchery seasons, larvae, tank biofilm, and rearing water samples were collected from control and probiotic-treated tanks in an oyster hatchery over a 12-day period after spawning. Samples were analyzed by 16S rRNA sequencing of the V4 or V6 regions followed by taxonomic classification, in order to determine bacterial community structures. There were significant differences in bacterial composition over time and between sample types, but no major effect of probiotics on the structure and diversity of bacterial communities (phylum level, Bray-Curtis k=2, 95% confidence). Probiotic treatment, however, led to a higher relative percent abundance of Oceanospirillales and Bacillus spp. in water and oyster larvae. In the water, an increase in Vibrio spp. diversity in the absence of a net increase in relative read abundance suggests a likely decrease in the abundance of specific pathogenic Vibrio spp., and therefore lower chances of a disease outbreak. Co-occurrence network analysis also suggests that probiotic treatment had a systemic effect on targeted members of the bacterial community, leading to a net decrease in potentially pathogenic species.